COMPARATIVE ANALYSIS OF DROUGHT TOLERANCE OF MEDICAGO L. PLANTS UNDER STRESSED CONDITIONS - Molor, Adiyasuren; Khajidsuren, Altantsetseg; Myagmarjav, Uuganzaya; Vanjildorj, Enkhchimeg (Mongolian Journal of Agricultural Sciences, 2017)
As a perennial forage crop, alfalfa (Medicago L.) can be cultivated in marginal lands and has a high yield and good quality of high-protein content. Alfalfa has deep vertical roots; this species is able to absorb even depth waters about 5 m depth and more. This advantage saves plant’s life in long term drought. The objective of this study was to compare the performance of drought stress during germination and growth stage of 2 species (Medicago sativa, Medicago falcata) and 2 varieties (Mongolian Medicago varia Marthz var.Burgaltai and Inner Mongolian Medicago varia Martyn var.Nutag Belcheer-2) in laboratory condition. In order to expose the drought stresses in plant by polyethylene glycol (PEG 4000) with 0 (control), -0.3, -0.5 and -1.0 MPa for 2 weeks respectively. The results represented that Medicago sativa had higher seed germination percentage than other species and varieties. Water uptake, dry matter index are observed in M.sativa higher than others. The highest chlorophyll content was in Medicago varia Marthz var.Burgaltai. The highest result of root, shoot length and weight were observed in Medicago sativa. In contrast, the significantly lowest result of morphological parameters was in Mediago varia Martyn var.Nutag Belcheer-2. M.sativa is highly tolerant to drought stress among species. M.varia Marth var.Burgaltai was moderately tolerant to drought stress among varieties.